Contextualizing medications for opioid use disorder and peer support service provision in the probation system with implementation science - Augustine W. Kang; Amelia Bailey; Siena Napoleon; Rosemarie Martin (BMC, 2024)
Abstract Background Medications for opioid use disorder (MOUD) is an evidence-based approach that reduces opioid-related mortality, particularly among criminal legal-involved persons who are at increased risk of adverse outcomes related to OUD. Implementing evidence-based approaches in the context of probation settings requires an in-depth understanding of specific contexts to improve intervention efficacy and effectiveness. Here, we use the Exploration, Preparation, Implementation, and Sustainment (EPIS) framework to understand implementation contexts for MOUD provision in the probation setting. Methods In-depth individual interviews were conducted with key programmatic stakeholders (treatment providers and probation staff involved in service provision for people on probation). The study examined stakeholder perspectives regarding MOUD and Peer Support Service (PSS) implementation among people who are involved in community supervision. Deductive and inductive thematic analysis was conducted, and subsequently the codes, subcodes, and themes were mapped onto the EPIS framework to better understand implementation contexts. Results We deduced key inner, outer, and bridging contexts that shape treatment service provision for individuals with OUD who are on probation. Inner contexts include a strong organizational climate that supports MOUD implementation and enthusiasm for peer support services. Outer contexts include difficulty navigating insurance among providers, treatment costs, and systemic stigma towards MOUD. Bridging contexts include a lack of collaboration/communication between relevant agencies (e.g., probation and courts). Conclusions Findings indicate the implementation is complex and requires a coordinated effort between correctional systems, probation agencies, and community-based treatment providers.